EVOLUTION OF A PORPHYRY-CU MINERALIZED MAGMA SYSTEM AT SANTA RITA, NEW MEXICO (USA) - Audétat A.; Pettke T. (My University, 2006)
The magmatic processes leading to porphyry-Cu mineralization at Santa Rita are reconstructed on the basis of petrographic studies, thermobarometry, and laser-ablation inductively-coupled-plasma mass-spectrometry analyses of silicate melt and sulfide inclusions from dikes ranging from basaltic andesite to rhyodacite. Combined results suggest that magma evolution at Santa Rita is similar to that of sulfur-rich volcanoes situated above subduction zones, being characterized by repeated injection of hot, mafic magma into an anhydrite-bearing magma chamber of rhyodacitic composition. The most mafic end-member identified at Santa Rita is a shoshonitic basaltic andesite that crystallized at 1000-1050°C, 1-3 kbar and log fO2 = NNO + 0.7 to NNO + 1.0, whereas the rhyodacite crystallized at 730-760°C and log fO2 = NNO + 1.3 to NNO + 1.9. Mixing between the two magmas caused precipitation of 0.1-0.2 wt % magmatic sulfides and an associated decrease in the Cu content of the silicate melt from 300-500 ppm to less than 20 ppm. Quantitative modeling suggests that temporal storage of ore-metals in magmatic sulfides does not significantly enhance the amount of copper ultimately available to ore-forming hydrothermal fluids. Magmatic sulfides are therefore not vital to the formation of porphyry-Cu deposits, unless a mechanism is required that holds back ore-forming metals until late in the evolution of the volcanic-plutonic system. © 2006 Oxford University Press.
Keywords: CULFUR; LA-ICP-MS; MAGMA MIXING; PORPHYRY-CU; SULFIDES